Maternal and neonatal outcome in preterm premature rupture of membranes - Truong, Thi Linh Giang; Vo, Quang Tan (Tạp chí Y Dược Huế, 2023)
Hue University, Vietnam Background: Preterm premature rupture of membranes is defined as rupture of membranes before the onset of labor with the gestational age < 37 weeks. Preterm premature rupture of membranes is associated with 10% of the perinatal mortality, particularly associated with respiratory distress syndrome and neonatal infection. Objective: The study aims to assess the outcome of maternal and fetal outcome in preterm premature rupture of membranes. Materials and Methods: This cross-sectional study was performed on 136 pregnant women complicated by preterm premature rupture of membranes during May 2020 to June 2022 at Hue University of Medicine and Pharmacy Hospital and Hue Central Hospital. The pregnant women were managed to accord the current clinical practice of hospital. The information about objects is recorded until the time of discharge. Results: The rate of vaginal delivery is 52.9% and intra-amniotic infection is 8.8%. The gestational age < 34 weeks and closed cervix are associated with a greater frequency of cesarean section. The rate of neonatal infection is 34%, respiratory failure is 30%. The gestational age < 34 weeks and prolonged duration of membrane rupture to delivery > 48 hours increase the risk of early neonatal infection and neonatal respiratory failure, while the delivery methods are not increased these risks. Conclusion: Our findings provide insights to physicians when counseling parents on preterm premature rupture of membranes at periviable gestational age.